Optimization of Biodiesel Production Process in Datura stramonium Seed Oil, a Non-edible Oil Source - T. Thangaraj2, Litty Koria1* and (Journal of Ecobiotechnology, 2010)
Abstract <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Biodiesel is an energy source suggested as an alternative to the diminishing fossil fuels. While research on the screening and identification of suitable energy candidates for biodiesel is on progress, optimization of the production process has to be considered for economic and environmental reasons. Transesterification is the process used for the conversion of triglycerides of oils and fats into fatty acid alkyl esters (biodiesel) and glycerine, in the presence of acid or alkali catalysts. Free fatty acid content, catalyst concentration, alcohol to oil molar ratio, reaction temperature and reaction time are the parameters that influence the production process of biodiesel. The optimization of reaction parameters is the primary step to be assessed in the production process of biodiesel. In the present investigation a detailed study on the optimization of catalyst concentration, alcohol to oil molar ratio, reaction temperature and reaction time has been carried out to determine the maximum conversion of oil to biodiesel, in a non-edible oil source, Citrullus colocynthis seed oil. The catalyst NaOH was used in varying proportions of 0.5, 0.75, 1.0 , 1.25 and 1.5 % (w/v ) of oil. The different molar ratios of methanol to oil studied were 3:1, 5:1, 7:1, 9:1 and 11:1. The reaction temperature assessed was between 40° and 90° C. The reaction time was varied from 30 minutes to 150 minutes. The maximum ester conversion in Datura stramonium oil was obtained at a catalyst concentration of 1.0% with an alcohol to molar ratio of 7:1 at a reaction temperature range of 60° and 70° C in the reaction time of two hours. --- 1Department of Zoology, L.R.G. Govt. Arts College for Women, Tirupur 641604 2Department of Zoology, Kongunadu Arts and Science College (Autonomous) Coimbatore 641029